CAPITALIZATION OF SOA HOUSE PROPERTY IN THE VILLAGE HEAD ELECTION IN OKI LAMA VILLAGE, NAMROLE DISTRICT, SOUTH BURU REGENCY - Talaohu, Ali Roho; Kalsum Consina (Gema Kampus IISIP YAPIS Biak, 2026)
This qualitative descriptive study aims to identify, understand, and explain how the capitalization of Soa House property is carried out in the Village Head election. The results show that, first, the background to the capitalization is the existence of political interests in the local political dynamics of the Village Head election. Second, in the Village Head election, political actors carry out social actions by utilizing Soa Houses as political capital. Keywords: Capitalization, Soa House, Village Head Election